TINGKAT KECEMASAN ATLET SEPAK BOLA KLUB GELORA FC SEBELUM BERTANDING - Awal Maulana; Lalu Suprawesta; Fitry Nachamory Oemar (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to describe the level of anxiety experienced by Gelora FC football athletes before competition. The study employed a quantitative approach with a descriptive survey design. The population consisted of 20 athletes, and the entire population was used as the research subjects. The instrument was a 35-item anxiety questionnaire covering physiological, cognitive, and behavioral-emotional aspects. The instrument testing indicated that all items were valid, with item-total correlations higher than the r-table value of 0.361, and the reliability coefficient reached Cronbach’s alpha = 0.884, indicating high internal consistency. Descriptive analysis showed that 18 athletes (90%) were in the high-anxiety category, 1 athlete (5%) was in the moderate category, and 1 athlete (5%) was in the very high category, while none were categorized as low anxiety. The mean interval score was 65, which falls within the high category. These findings indicate that most Gelora FC athletes have not yet reached optimal mental readiness before competition. Therefore, structured mental training is recommended to help athletes manage anxiety and maintain competitive performance.